Hygrocybe monscaiensis sp nov, de la subsección Squamulosae (Bataille) Singer - Palazón Lozano, Fernando; Tabarés Carriedo, Manuel; Rocabruna i Llavanera, August (Revista Catalana de Micologia, 2007)
Hygrocybe monscaiensis sp nov of the subsection squamulosae (Bataille) Singer. We describe, comment and illustrate a new species, in the subsection squamulosae (Bataille) Singer, with evident differences macroscopic, microscopic, arid ecological, with the neighbour taxa: H. Caleiphda Amolds H. Corsica Candusso, H. Miniata (Fr.: Fr:) Kummer, H. Helobia (Amolds) Bon and H. Rhodophylla Kuhner.